Opioid free onco-anesthesia: Is it time to convict opioids? A systematic review of literature - Raghu S Thota; Seshadri Ramkiran; Rakesh Garg; Jyotsna Goswami; Vaibhavi Baxi; Mary Thomas (Wolters Kluwer Medknow Publications, 2019)
The epidemic of opioid crisis started getting recognised as a public health emergency in view of increasing opioid-related deaths occurring due to undetected respiratory depression. Prescribing opioids at discharge has become an independent risk factor for chronic opioid use, following which, prescription practices have undergone a radical change. A call to action has been voiced recently to end the opioid epidemic although with the pain practitioners still struggling to make opioids readily available. American Society of Anesthesiologist (ASA) has called for reducing patient exposure to opioids in the surgical setting. Opioid sparing strategies have emerged embracing loco-regional techniques and non-opioid based multimodal pain management whereas opioid free anesthesia is the combination of various opioid sparing strategies culminating in complete elimination of opioid usage.The movement away from opioid usage perioperatively is a massive but necessary shift in anesthesia which has rationalised perioperative opioid usage. Ideal way moving forward would be to adapt selective low opioid effective dosing which is both procedure and patient specific while reserving it as rescue analgesia, postoperatively. Many unknowns persist in the domain of immunologic effects of opioids, as complex interplay of factors gets associated during real time surgery towards outcome. At present it would be too premature to conclude upon opioid-induced immunosuppression from the existing evidence. Till evidence is established, there are no recommendations to change current clinical practice. At the same time, consideration for multimodal opioid sparing strategies should be initiated in each patient undergoing surgery.